A Survey of Fog Computing Architecture and Its Applications - Bano, Mehnaz (International Journal of Computer Sciences and Engineering, 2020)
Now days we can observe that so many advancements are happening in the technologies and new Generations using various programs, software and applications are progressively complicated and needs lower latency requirements. So that clients would be able to get to these applications and information from anyplace at any time without any delay. Cloud computing is one of these technologies designed to deliver computer resources platforms and other various computing facilities. In this on –demand services are provided to the users through the Internet. But network dependency, data security issues, lower bandwidth, variation of cost, location-awareness are some limitations that we are facing with cloud computing. To overcome inherent problems of this popular computing paradigm fog computing has come up as a promising framework to provide flexible and adaptable resources adjacent to network. Fog computing is generally an idea of a distributed network that brings the cloud services that are communication, computation and storage near upon edge devices and users. It is used to improve efficiency and Real-time processing of data. The major objective of fog computing is to shorten the particular data that should be delivered to the cloud for processing, study, storage and computational purpose. And at the present moment, fog computing appears to be the most alternate available that can handle all client requirements.